Identification of neural cells activated by mating stimulus in the periaqueductal gray in female rats - Yamada, Shunji; Kawata, Mitsuhiro (Frontiers in Neuroscience, 2014)
Induction of lordosis as typical female sexual behavior in rodents is dependent on a mount stimulus from males and blood levels of estrogen. Periaqueductal gray (PAG) efferent neurons have been suggested to be important for lordosis behavior; however, the neurochemical basis remains to be understood. In this study, we neuroanatomically examined 1) whether PAG neurons activated by mating stimulus project to the medullary reticular formation (MRF), which is also a required area for lordosis; and 2) whether these neurons are glutamatergic. Mating stimulus significantly increased the number of cFos-immunoreactive (ir) neurons in the PAG, particularly in its lateral region. Half of cFos-ir neurons in the lateral PAG were positive for a retrograde tracer (FluoroGold; FG) injected into the MRF. cFos-ir neurons also colocalized with mRNA of vesicular glutamate transporter 2 (vGLUT2), a molecular marker for glutamatergic neurons. Using retrograde tracing and in situ hybridization in conjunction with fluorescent microscopy, we also found FG and vGLUT2 mRNA double-positive neurons in the lateral PAG. These results suggest that glutamatergic neurons in the lateral PAG project to the MRF and are involved in lordosis behavior in female rats.